Electrical conductivity of p-type BiOCl nanosheets1. Issue 13 (14th February 2015) - Myung, Yoon; Wu, Fei; Banerjee, Sriya; Park, Jeunghee; Banerjee, Parag
<x xml:space="preserve">Abstract</x> BiOCl nanosheets were synthesized using a facile hydrolysis method and their p-type electrical conduction as a function of oxygen partial pressure was measured.